Quantitative trait loci for root morphology traits under aluminum stress in common bean (Phaseolus vulgaris L.) - López Marin, H.D.; Rao, Idupulapati M.; Blair, Matthew W. (Springer, 2009)
Aluminum (Al) toxicity is a major limiting factor of crop production in acid soils, which are found mostly in developing countries of the tropics and sub-tropics. Common bean (Phaseolus vulgaris L.) is particularly sensitive to Al toxicity; and development of genotypes with better root growth in Al-toxic soils is a priority. The objectives of the present study were to physiologically assess root architectural traits in a recombinant inbred line (RIL) population of common bean that contrasts for Al resistance (DOR364 × G19833) and to identify quantitative trait loci (QTL) controlling root growth under two nutrient solutions, one with 20 ?M Al concentration and the other without Al, both at pH 4.5. A total of 24 QTL were found through composite interval mapping analysis, 9 for traits under Al treatment, 8 for traits under control treatment, and 7 for relative traits. Root characteristics expressed under Al treatment were found to be under polygenic control, and some QTL were identified at the same location as QTL for tolerance to low phosphorous stress, thus, suggesting cross-links in genetic control of adaptation of common bean to different abiotic stresses.